Abstracts - Key words - Malaspina, Ermanno (Ciceroniana On Line, 2018)
I volumi contenenti Atti sono disponibili con proprio ISBN nel sito http://www.collane.unito.it/oa/collections/show/6 sei mesi dopo la pubblicazione del numero corrispondente della Rivista. Les volumes contenant des Actes sont disponibles avec leur propre ISBN sur http://www.collane.unito.it/oa/collections/show/6 six mois après la publication du numéro correspondant de la Revue. The volumes containing Proceedings are available with their own ISBN at http://www.collane.unito.it/oa/collections/show/6 six months after publication of the corresponding issue of the Journal.